Performance Analysis of Transform University Studies in Indonesia Context - Wolok, Eduart; Siregar, Hermanto; Djohar, Setiadi; Baga, Lukman M. (JDM (Jurnal Dinamika Manajemen), 2018)
The purpose of this study are to analyze the performance of Universitas Negeri Gorontalo (UNG) in the financial and academic aspects; to analyze the gaps in financial performance and academic performance; and to know the differences in financial performance and academic performance before and after transformation into a State Universities Public Service Agency (PTN BLU). The analysis method used are descriptive analysis, gap analysis by calculating the average expected service level, and average calculation for perceived service actual performance, and t-test. The result of the research shows that the implementation of governance especially in the case of service is increasing and efficient. Besides that, after the transformation into BLU,UNG shows various progress, especially the improvement of financial performance as measured from income level from Non-Tax Revenue (PNBP), and from Revenue Budget and State Expenditure (APBN), while the academic performance, measured from 12 indicators covering tri darma of higher education, has increased significantly compared to when UNG is still part of the Work Unit (SATKER). While the results of gap analysis show that the academic and financial performance perceived by lecturers and UNG employees is higher than the quality of expectedservice. The financial performance of UNG before and after BLU has significant differences, as well as the academic performance.